Cost-effectiveness of liver transplantation versus last-resort systemic therapy for colorectal liver metastases. Issue 6 (12th March 2022) - Bjørnelv, Gudrun M W; Zolic-Karlsson, Zinajda; Dueland, Svein; Line, Pål-Dag; Aas, Eline
Abstract : This study estimated the cost-effectiveness of liver transplantation in patients with colorectal liver metastases confined to the liver with progressive disease, compared with alternative treatment options: TAS-102, regorafenib, or best supportive care. Using a mathematical simulation model, people's life expectancy and healthcare costs over 25 years were estimated. Transplanted patients lived for 4.28 years, more than 3 years longer than those who received alternative treatment options. Despite this, the high cost of liver transplantation meant that this treatment was cost-effective only at high willingness-to-pay thresholds.